Current-sharing Design of Special Rectifier Power Supply - CHEN Yuanchu; ZHANG Min; ZENG Qiusheng; LU Ka; CHEN Jielian; QIN Jianmin (Kongzhi Yu Xinxi Jishu)
It presents a design and calculation method of current-sharing for parallel-circuit of special rectifier power-supply. Currentsharing simulation and test of thysistor parallel-arm circuit were taken based on the special test power-supply design of a university, which can be used as a reference in current-sharing design of high power rectifier system.